An Economic Theory of Labor Discrimination (2021)
This article presents a theory of labor discrimination based on the behavior of economic agents that maximize utility and profits. The article makes use of a monopsony that hires workers that have the same labor productivity, to focus on perfect discrimination; discrimination by quantities of labor hired; and discrimination by types of labor hired. The article concludes that in such contexts, workers with the same productivity may be discriminated in wages and quantities of labor hired, when firms make use of their market power; when there are differences in the opportunity costs and the wage elasticities of labor supply among workers; when there is asymmetric information, self-selection and adverse selection; and when firms or governments decide not to allow for wage discrimination. First best minimum wages may contribute to improve employment and welfare, but higher minimum wages may not.